The Future of Equity, Diversity, and Inclusion (EDI) in Education: Keep, Reform, or Dismantle? - Eizadirad, Ardavan; Walton, Gerald (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2025)
Equity, Diversity, and Inclusion, also known as EDI, is one of several acronyms that refer to policies and practices of organizations, such as K to 12 school boards and post-secondary institutions, to promote inclusive and equitable environments. While EDI has become a ubiquitous discourse in educational administration, its impact extends into classroom pedagogies, hiring practices, curriculum development, and institutional culture. In this article, we critically examine the extent to which EDI committees and initiatives fulfil their promise of fostering inclusive environments to support equity-denied groups. We address the following research questions: (1) How have EDI frameworks evolved in education? (2) What gaps exist between EDI policies and their implementation for transformative impact? (3) What alternative approaches can create sustainable and impactful change? Overall, the article casts a critical eye on EDI initiatives, exploring opportunities, challenges, and potential futurities considering the polarizing discourse of political correctness and anti-wokeness.